Ocular and multicentric T-cell lymphoma in horse - Oliveira, Mariana C.; Faleiro, Rayssa D.; Santos, Cinthia C.A.; Oliveira, Gabriela F.; Daoualibi, Yasmin; Sonne, Luciana; Brito, Marilene F.; Ubiali, Daniel G. (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Oliveira M.C., Faleiro R.D., Santos C.C.A., Oliveira G.F., Daoualibi Y., Sonne L., Brito M.F. & Ubiali D.G. [Ocular and multicentric T-cell lymphoma in horse.] Linfoma de células T multicêntrico e ocular em equino. Revista Brasileira de Medicina Veterinária, 38(Supl.2):147-151, 2016. Setor de Anatomia Patológica, Departamento Epidemiologia e Saúde Pública, Universidade Federal Rural do Rio de Janeiro, BR 465 Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: danielubiali@hotmail.com A 10-year-old gelding, mixed breed had body score condition 3 (1-10), with reluctance to move due to the loss of visual acuity in both eyes, right eye swelling and marked dyspnea. The ophthalmic examination showed no response to threat of reflection, objects test or direct reflection and consensus of both eyes. Examination with visor magnifier and Finoff transilluminator revealed buftalmia, hyphema, aqueous flare, corneal neovascularization and posterior synechiae with irregular bulging of the iris in the right eye and aqueous flare, central anterior synechiae and mature cataract in the left eye. It was found corneal integrity in both eyes with the fluorescein test. Urine sample submitted for PCR to Leptospira sp. resulted negative. Euthanasia was performed after unsuccessful treatment attempts. At necropsy there was a mass in the right eyeball, the pleural surface of the diaphragm and the mesentery. There was multifocal to coalescing whitish nodules between 1 and 4 cm in diameter in the lung, filling about 80% of the lungs’ surface, mainly in the ventral region. Morphology of masses was histopathologically compatible with lymphoma. Anti-CD3 antibody resulted positive in all samples analyzed characterizing immunophenotypic T-cell lymphoma.